Mapping of MeLiM melanoma combining ICP-MS and MALDI-MSI methods - Vaníčková, Lucie; Do, Tomáš; Vejvodová, Markéta; Horák, Vratislav; Hubálek, Martin; Emri, Gabriella; Zemánková, Kristýna; Pavelicová, Kristýna; Křížková, Soňa; Faltusová, Veronika; Pompeiano, Antonio; Vaculovičová, Markéta; et al. (International journal of biological macromolecules, 2022)
Here we developed a powerful tool for comprehensive data collection and mapping of molecular and elemental signatures in the Melanoma-bearing Libechov Minipig (MeLiM) model. The combination of different mass spectrometric methods allowed for detail investigation of specific melanoma markers and elements and their spatial distribution in tissue sections. MALDI-MSI combined with HPLC-MS/MS analyses resulted in identification of seven specific proteins, S100A12, CD163, MMP-2, galectin-1, tenascin, resistin and PCNA that were presented in the melanoma signatures. Furthermore, the ICP-MS method allowed for spatial detection of zinc, calcium, copper, and iron elements linked with the allocation of the specific binding proteins.
Keywords: prasata; tandemová hmotnostní spektrometrie; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Swine; Melanoma; proteiny; Animals; Tandem Mass Spectrometry; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; melanom; Proteins; Swine, Miniature; zvířata; miniaturní prasata